Post-mortem peripheral smear: A forensic diagnostic tool? - Chandra Deepak, G; Ananth Rupesh , Kattamreddy; Taqiuddin Khan , M (Journal of Indian Academy of Forensic Medicine, 2021)
The current study of post-mortem peripheral smears was conducted in Department of Forensic Medicine, Osmania Medical College  with the main objective of studying the seasonal variability of autolysis of cell lines in peripheral circulation. In the study sample of  73 subjects, peripheral smears were made in the morgue immediately after collecting blood by venepuncture. Smears were stained  with Leishman stain (A Romanowsky stain) within 2 hours of preparation and light microscope was used to study changes. The  changes in cell morphology, membrane integrity, cytoplasmic and nuclear changes were studied in detail using valuable information  from previous studies and conclusions were arrived at. At the outset white blood cells are most suitable for TSD predictability among  others in peripheral smear because they withstand extraneous variables like refrigeration and show a similar degree of autolytic  changes across all seasons. The validity of all such studies on cell lines for TSD was discussed from medico legal perspective. The  take home message is all the microscopic changes studied in present study provided no added advantage significantly apart from  traditional gross changes like rigor mortis, algor mortis, post-mortem lividity. If properly used on regular basis, algor mortis can  enhance the quality of our reporting in India with respect to TSD.
Keywords: Post-mortem peripheral smear; Time since death; Microscopic forensics